2020
DOI: 10.1177/0033294120964055
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Implicit Math Anxiety on Math Achievement

Abstract: Previous work has noted that math anxiety may have a profound effect on math performance; however extant research has relied on measures that explicitly assess math anxiety. This study examined the effects of implicit math anxiety on the performance of a math achievement task. We hypothesized that combined measure of implicit anxiety and explicit anxiety would better predict math achievement than measures of explicit math anxiety alone. In addition, we hypothesized that an individuals’ measured implicit anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In addition to the psychological feelings, students who experience mathematics anxiety may also have physical reactions, like sweating and pain. Previous literature documented the negative effects of mathematics anxiety on student academic motivations, attitudes toward mathematics, mathematics achievement, and future mathematical learnings ( Gierl and Bisanz, 1995 ; Luo et al, 2014 ; Wu et al, 2014 , 2017 ; Carey et al, 2016 ; Ramirez et al, 2018 ; Namkung et al, 2019 ; Donolato et al, 2020 ; Pantoja et al, 2020 ; Westfall et al, 2020 ; Barroso et al, 2021 ). Recently, Barroso et al (2021) conducted a meta-analysis of the relationship between mathematics anxiety and student mathematics achievement across the studies from 1992 to 2018, and found a general negative correlation, i.e., r =–0.28, between them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the psychological feelings, students who experience mathematics anxiety may also have physical reactions, like sweating and pain. Previous literature documented the negative effects of mathematics anxiety on student academic motivations, attitudes toward mathematics, mathematics achievement, and future mathematical learnings ( Gierl and Bisanz, 1995 ; Luo et al, 2014 ; Wu et al, 2014 , 2017 ; Carey et al, 2016 ; Ramirez et al, 2018 ; Namkung et al, 2019 ; Donolato et al, 2020 ; Pantoja et al, 2020 ; Westfall et al, 2020 ; Barroso et al, 2021 ). Recently, Barroso et al (2021) conducted a meta-analysis of the relationship between mathematics anxiety and student mathematics achievement across the studies from 1992 to 2018, and found a general negative correlation, i.e., r =–0.28, between them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Math anxiety is defined as feelings of tension, anxiety, or even fear that interfere with numbers and math-related problem solving (Westfall, McAuley, & Millar, 2020). In addition, individuals who experience math anxiety are characterized by negative self-talk that they cannot control (Godbye dalam (Saputra, 2017).…”
Section: 037mentioning
confidence: 99%
“…Moreover, existing studies have tended to either measure MA explicitly using self-report measures or assume changes in behavioural outcomes (such as maths performance) are indirectly accounted for by changes in MA. However, findings have demonstrated that maths achievement is better predicted by implicit and explicit MA combined [91]. Therefore, it may be necessary for future intervention work to include both implicit and explicit measures of MA in order to fully understand attempts to address MA.…”
Section: Future Directionsmentioning
confidence: 99%